The Smallmouth Bass Population and Fishery in a Northern Wisconsin Lake, Clear Lake, Oneida County - Marinac, Patricia (University of Wisconsin-Stevens Point, 1976)
Smallmouth bass (Micropterus dolomieui) were captured in fvke nets and tagged in Clear Lake, Oneida County, Wisconsin. A creel survey was conducted to obtain information pertaining to the fishery. Fyke net samples for 1974 and 1975 consisted of 98 and 96 percent of fish in age classes I through IV. Total lengths at annuli I through XI were 92, 142, 185, 240, 297, 354, 394, 427, 453, 473, and 487 mm. Smallmouth bass spawned in late June, when the water temperature approached 19°C. Crayfish was the most important food item and comprised 74 percent by number and 65 percent by volume of the contents of stomachs containing food. Total annual mortality rates, calculated using catch curves, were 78 percent in 1974 and 77 percent in 1975. The exploitation rate, which was corrected for tag loss, was 42 percent for bass over 225 mm lonq, for 1974 and 1975 combined. Exploitation rates for length groups were: 37 percent (225 - 305 mm), 85 percent (306 - 357 mm), and 43 percent (358 mm and above). Estimates of total fishing ores sure were 49 and 36 hours per hectare in 1974 and 1975. Catch rates were 5 and 7 smallmouth bass for 100 hours of effort. Mean length of creeled smallmouth bass was 200 mm in both years. The harvest, estimated in two ways in the two years, ranged from 729 (2.1 bass/ha} to 1307 small mouth bass (3.8 bass/ha). Smallmouth bass less than 300 mm long (aqe classes I through IV) made up 98 percent of the anglers' harvest in 1974 and 97 percent in 1975. Population estimates, calculated from creel survey data, were 3237 (9.5/ha) and 2723 (8.0/ha) smallmouth bass over 225 mm long in 1974 and 1975. Production per unit recruitment was estimated to be 1265 grams per 1000 grams. Length limits of 240, 297, 322, and 354 mm would increase the weight harvested by 2, 13.5, 13.8, and 14.4 percent over the present no limit regulation, based on calculations of equilibrium yield per unit recruitment.